Emergent transition from face-to-face to online learning in a South African University in the context of the Coronavirus pandemic - Mpungose, Cedric B. (Humanities & social sciences communications, 2020)
South African universities have been forced to transit from face-to-face to online learning (e-learning) as a result of the coronavirus pandemic (COVID-19). However, various challenges hinder disadvantaged students from realising the full potential of e-learning. Therefore, this study’s main objective is to propose alternative pathways to overcome such challenges for students, to enable them to have access to effective e-learning. This study draws on a two-year postdoctoral qualitative research project conducted at a South African university to explore students’ experiences of the transition from face-to-face to e-learning. Twenty-six students completing a curriculum studies programme were purposively and conveniently sampled to generate data using e-reflective activity, Zoom group meetings and a WhatsApp one-on-one semi-structured interview. Findings articulate the digital divide as a hindrance to students realising the full potential of e-learning, yet lecturers still want students to submit assessment tasks and engage with course activities on the Moodle learning management system. With universities using face-to-face learning becoming vulnerable to the COVID-19 pandemic and other challenges which result in a shutdown of university sites, alternatives need to be sought to allow students, particularly disadvantaged students, to realise e-learning.